Fertilization of bovine oocytes vitrified pre- and post in vitro maturation - Faizah, Zakiyatul; Darsini, Ninik; Hinting, Aucky (Folia Medica Indonesiana, 2017)
The success rate of fertilization post save frozen oocytes is still very low, because the oocyte has distinctive features, namely the volume ratio and a lower surface to the limited penetration of water and cryoprotectants penetrate cells. Beside mature oocytes have a thread spindles are particularly vulnerable to the drop in temperature. Keep frozen oocytes is needed, especially in women who needed rescue fertility so their oosit can be fertilized. Maturation is done in TC 100 mL medium covered with mineral oil in a petri dish with a diameter of 36 mm. Oocyte vitrification begins with washing in PBS supplemented medium serum 20% for 1-2 minutes, followed by serum in the medium PBS + 20% + 10% ethylene glycol for 10-14 minutes. Then oocyte vitrification medium is transported in PBS + serum 20% + sucrose 0.5M ethylene glycol + 15% + 15% PROH for 25-30 seconds. Thawing oocytes is done by successive immersed in the media: 1). PBS + 20% serum + 0.5M sucrose, 2). PBS + 20% serum + 0.25M sucrose, and 3). PBS + 20% serum + 0.1 M sucrose. Insemination is done in rosset, and the number of fertilization was observed after 48 hours. Fertilization in the control group amounted to 42.97%, while the K1 and K2 there are no fertilization at all. The analysis showed that fertilization in the control and treatment groups significantly different at p <0.05 in both treatment groups K1 or K2 there are no fertilization at all. The conclusions of this study is there is no difference between the amount of fertilization of bovine oocytes were vitrified pre and post-maturation in vitro.